Iklan, Becoming White, Atribut I ANALISIS SEMIOTIKA FENOMENA BECOMING WHITE DAN ISLAMIC ATTRIBUTE PADA IKLAN GIV WHITE HIJAB (Pendekatan Roland Barthes) - arisandi, Nadiya; Patminingsih, Astuti (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Abstract: Advertising plays a crucial role in disseminating cultural values and ideologies. One emerging phenomenon in beauty product advertisements is becoming white, which refers to the idealization of fair skin as a beauty standard. Simultaneously, Islamic attributes are often utilized in marketing strategies to attract Muslim consumers. This article aims to analyze the representation of the becoming white phenomenon and Islamic attributes in the GIV White Hijab advertisement. Using Roland Barthes' semiotic approach, this study explores the denotative and connotative meanings embedded in the advertisement's visual and textual elements. The analysis reveals that the advertisement does not merely promote a skin-whitening product but also reproduces the ideology of colorism and instrumentalizes religious symbols. The depiction of light-skinned women wearing the hijab reinforces discriminatory beauty standards and constructs a problematic myth about the ideal identity of Muslim women. The study concludes that advertisements serve as powerful tools for spreading hegemonic discourse, which in this case, contributes to harmful and exclusionary representations, particularly toward darker-skinned Muslim women. These findings highlight the need for critical awareness of how media representations shape social perceptions of beauty and religious identity. Keywords: Advertisement; Becoming White; Islamic Attribute; Semiotics; Roland Barthes. Abstrak: Iklan merupakan media yang berperan penting dalam menyebarkan nilai-nilai budaya dan ideologi. Salah satu fenomena yang muncul dalam iklan produk kecantikan adalah becoming white, yaitu kecenderungan mengidealkan kulit putih sebagai standar kecantikan. Di sisi lain, atribut Islam juga sering dimanfaatkan dalam strategi pemasaran untuk menarik konsumen Muslim. Artikel ini bertujuan untuk menganalisis representasi fenomena becoming white dan atribut keislaman dalam iklan GIV White Hijab. Penelitian ini menggunakan pendekatan semiotika Roland Barthes untuk mengungkap makna denotatif dan konotatif dari elemen-elemen visual dan tekstual dalam iklan tersebut. Hasil analisis menunjukkan bahwa iklan tidak hanya mempromosikan produk pemutih kulit, tetapi juga mereproduksi ideologi colorism dan menginstrumentalisasi simbol-simbol keislaman. Representasi model perempuan berjilbab dengan kulit putih menegaskan standar kecantikan yang diskriminatif dan membentuk mitos tentang identitas ideal perempuan Muslim. Penelitian ini menyimpulkan bahwa iklan dapat menjadi sarana penyebaran wacana yang bersifat hegemonik, yang dalam kasus ini berpotensi menimbulkan representasi yang merugikan dan diskriminatif terhadap kelompok tertentu, khususnya perempuan Muslim dengan warna kulit gelap. Kata Kunci: Iklan; Becoming White; Atribut Islami; Semiotika; Roland Barthes.